Developments in Hydrogen Fuel Cells - Abdul Ghani Olabi; Enas Taha Sayed (Energies, 2023)
The rapid growth in fossil fuels has resulted in climate change that needs to be controlled in the near future. Several methods have been proposed to control climate change, including the development of efficient energy conversion devices. Fuel cells are environmentally friendly energy conversion devices that can be fuelled by green hydrogen, with only water as a by-product, or by using different biofuels such as biomass in wastewater, urea in wastewater, biogas from municipal and agricultural wastes, syngas from agriculture wastes, and waste carbon. This editorial discusses the fundamentals of the operation of the fuel cell, and their application in various sectors such as residential, transportation, and power generation.